Is urban food demand in the Philippines different from China? - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2014)
It is essential to understand the consumption pattern of food and how it changes over time to formulate sound economic policies as well as marketing and pricing strategies. In this study, we estimate the Quadratic Almost Ideal Demand System with six rounds of the Family Income Expenditure Survey exploiting the conditional linearity of the demand system. We find that the Filipino diet has become westernized and that the changes in urban food demand elasticities are qualitatively similar to those in urban China, especially for meat, fruits, and vegetables.We also offer some policy and business implications.